ANALISIS TOKOH KAGURA SEIICHIRO NOVEL REAL FACE KARYA CHINEN MIKOTO - Muliani Moeliono; Wayan Nurita; Ladycia Sundayra (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2023)
This study aims to determine the personality of Hiiragi Takayuki using Sigmund Freud's Psychoanalytic theory in the novel Real Face. This study used descriptive qualitative method. The primary data source of this research is the novel Real Face. The data obtained were analyzed using psychoanalytic theory, namely id, ego, super ego. The method used in this study uses the listen and note method. For the presentation of the data, an informal method was used, namely data in the form of dialogues and Japanese narration which were translated into Indonesian. The results show that the personality theory experienced by the character Kagura Seiichiro is, the id is shown through Kagura's desire to achieve her wish, the ego is shown to arise when Kagura's conscience wants to refuse, the super ego arises when Kagura Seiichiro thinks that the proposal offered by Hiiragi is unreasonable.